Fundamentos jurídicos da zona de amortecimento em terra indígena - Pascuchi, Priscila Mari (2007)
The objective of the work is the protection of the negative environmental impacts, resulting of the adjacent area, on the environmental resources in indigenous land. Though a study about the need of juridically implementation of the buffer zone in the indigenous land. The indigenous land is not considered a territorial space destined to the environmental conservation, however, it should provide to the indigenous society an environment ecologically balanced. With that, the conservation is requested from their necessary environmental resources to the indigenous well-being. The buffer zone in the indigenous land, it should consist of the territorial ordination of its neigborhood for ZEE (Ecological- Economical Zoning), in way to protect the indispensable environmental resources to the indigenous societies. The buffer zone also tends to insert the indigenous lands in ecological corridors, for the end of avoiding the insularization of the same ones. The impacts environmental negative resulting of the area outskirts of the I spill of the indigenous land are caused by antropic activities or by demarcation of the indigenous land, which can transform it in a forest fragment. In conclusion it was observed that the juridical norms of environment conservation the indigenista right and environmental factors bring juridical foundation for implementing the buffer zone. Key words: Indigenous lands, indigenist rights, buffer zone, territorial spaces especially protected, Units of Conservation and environmental conservation.